Analisis dan Perancangan Sistem Repositori Tugas Akhir Studi Kasus STT Terpadu Nurul Fikri menggunakan Framework Website MVC - Miftakhul Aris; Yekti Wirani (LPPM STT Terpadu Nurul Fikri, 2020)
This final project repository information system is an idea that emerged to assist STT NF in managing the final project archiving, which was previously conventionally a new and modern digital system. The final project repository information system is a system that is expected to help STT NF organize the archiving of last assignment data that have done to be neater, safer, and easier to manage. Developed using the unified process method and object-oriented analysis modeling, then implemented using the PHP programming language and YII framework. The result of this study is a website-based final project repository system that can archive student last project data and can be used to search and display existing last project data through the admin or user interface; in this case, students.